Varicella Exposure in Neonatal Intensive Care Unit in a Low Resource Country: Successful Prophylaxis with Intravenous Immunoglobulins - Manar Al-lawama; Asma Almustafa; Ala Elrimawi; Amal Bani Mustafa; Suzan Almomani; Eman Badran (Mashhad University of Medical Sciences, 2019)
Background: Varicella-zoster infection is a serious and potentially fatal disease, especially among newborns.Several studies have described postnatal varicella zoster exposure among neonates and reported on the efficacy of varicella-zoster immunoglobulins (VZIG) used as post-exposure prophylaxis. Unfortunately, VZIG is not available in Jordan. A limited number of studies have investigated the efficacy of intravenous immunoglobulins (IVIG) as an alternative preventive post-exposure to the varicella virus. Methods: This retrospective descriptive study was conducted to review the outcomes of two separate incidents of varicella-zoster exposure and the prophylactic use of IVIG in the neonatal intensive care unit in Jordan. Results: The sources of exposure in both incidents infected medical health workers. During the exposure, cohort measures were applied to neonates whose mothers did not receive immune prophylaxis against IVIG. Newborns were followed appropriately. Totally, 22 cases were identified representing two exposure incidents without a varicella-zoster infection. Conclusion: The results indicated that IVIG was an effective prophylactic therapy for neonates post varicella virus exposure.